Ability of patients with acute ischemic stroke to recall given information on intravenous thrombolysis: Results of a prospective multicenter study. (March 2023) - Schuster, Luzie; Essig, Fabian; Daneshkhah, Naeimeh; Herm, Juliane; Hellwig, Simon; Endres, Matthias; Dirnagl, Ulrich; Hoffmann, Frank; Michalski, Dominik; Pfeilschifter, Waltraud; Urbanek, Christian; Petzold, Gabor C; et al.
Introduction: Intravenous thrombolysis (IVT) is an on label treatment for selected patients with acute ischemic stroke (AIS). As major bleeding or allergic shock may occur, the need to ensure patients' informed consent for IVT is a matter of debate. Patients and methods: Prospective investigator-initiated multi-center observational study to assess the ability of AIS patients to recall information, provided by a physician during a standardized educational talk (SET) on IVT use. The recall of 20 pre-defined items was assessed in AIS after 60–90 min ( n = 93) or 23–25 h ( n = 40) after SET. About 40 patients with subacute stroke, 40 non-stroke patients, and 23 relatives of AIS patients served as controls, and were surveyed 60–90 min after SET. Results: Within 60–90 min after SET, AIS patients (median age 70 years, 31% female, median NIHSS score on admission 3 points) who were considered capable to provide informed consent recalled 55% (IQR 40%–66.7%) of the provided SET items. In multivariable linear regression analysis recapitulation by AIS patients was associated with their educational level (β = 6.497, p < 0.001), self-reported excitement level (β = 1.879, p = 0.011) and NIHSS score on admission (β = −1.186, p = 0.001). Patients with subacute stroke (70 years, 40% female, median NIHSS = 2) recalled 70% (IQR 55.7%–83.6%), non-stroke patients (75 years, 40% female) 70% (IQR 60%–78.7%), and AIS relatives (58 years, 83% female) 70% (IQR 60%–85%). Compared to subacute stroke patients, AIS patients less often recalled the frequency of IVT-related bleeding (21% vs 43%), allergic shock (15% vs 39%), and bleeding-related morbidity and mortality (44% vs 78%). AIS patients recalled 50% (IQR 42.3%–67.5%) of the provided items 23–25 h after SET. Conclusion: AIS patients eligible for IVT remember about half of all SET-items after 60–90 min or 23–25 h, respectively. The fact that the recapitulation of IVT-associated risks is particularly poor should be given special consideration.